2016
DOI: 10.1021/acscatal.6b02290
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophosphination of Unactivated Alkenes and Alkynes Using Iron(II): Catalysis and Mechanistic Insight

Abstract: The catalytic addition of phosphines to alkenes and alkynes is a very attractive process that offers access to phosphines in a 100% atom-economic reaction using readily available and inexpensive materials. The products are potentially useful ligands and organocatalysts. Herein we report the first example of intramolecular hydrophosphination of a series of non-activated phosphino-alkenes and phosphino-alkynes with a simple iron β-diketiminate complex. Kinetic studies suggest that this transformation is first or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 46 publications
2
61
0
Order By: Relevance
“…Our own research has focused on transformations with phosphorus, furnishing examples of intermolecular 34 and intramolecular 35 hydrophosphination. For intramolecular hydrophosphination, the challenge primarily lies in synthesis of the starting materials, but once prepared, pre-catalyst 15 (Fig.…”
Section: Ironmentioning
confidence: 99%
See 1 more Smart Citation
“…Our own research has focused on transformations with phosphorus, furnishing examples of intermolecular 34 and intramolecular 35 hydrophosphination. For intramolecular hydrophosphination, the challenge primarily lies in synthesis of the starting materials, but once prepared, pre-catalyst 15 (Fig.…”
Section: Ironmentioning
confidence: 99%
“…7). 47 The authors found that alkyl substituents on the aryl ligand functionality (35) led to C-H activation in the presence of an azide aminating reagent, thus preventing formation of the key nitrene intermediate need for amination of substrate (e.g. LCuvNAd), whereas this was circumvented with the 2,6-dichloro ligand.…”
Section: Coppermentioning
confidence: 99%
“…β‐diketiminates with sterically demanding groups have been successfully employed in the synthesis of low‐coordinate iron complexes. In contrast to a large number of heteroleptic β‐diketiminato iron complexes with alkyl, aryl, vinyl, amido and imido co‐ligands, the chemistry of iron β‐diketiminato complexes featuring phosphido co‐ligands is largely unexplored . Notably, the closest analogs of phosphido complexes reported by Holland and co‐workers are iron complexes with NR 2 groups, which exhibit interesting structural properties and reactivity …”
Section: Introductionmentioning
confidence: 99%
“…Reports by Webster et al, , , on the use of an iron(II) β‐diketiminato pre‐catalyst, [(Dippnacnac)Fe(CH 2 TMS)] for the hydrophosphination of unsaturated hydrocarbons and dehydrocoupling of primary and secondary phosphines postulated the formation of an intermediate terminal phosphido complex. In the case of hydrophosphination, the authors proposed that the active catalyst is a monomeric phosphido complex; however, the active species was isolated as a bridging complex, [(Dippnacnac)Fe(PRH(CH 2 ) 3 CH=CH 2 )] 2 . Worth emphasizing is that this compound is not only the first β‐diketiminate iron complex bridged by phosphido groups, but also a perfect example highlighting the catalytic potential of low‐coordinate iron compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal catalyzed hydrophosphination is an economical route for atoms to access a range of functionalized phosphines from alkenes and alkynes [1][2][3]. We have already demonstrated the efficacy of β-diketiminate iron catalysts in hydrophosphination [4,5], and questioned whether, given the ease with which these complexes can be synthesized, the reactivity could be extended to other first row transition metal β-diketiminate complexes. Nickel is an ideal metal to choose for this purpose: Holland has described an easy, scalable synthetic route to the N(SiMe 3 ) 2 -ligated complex (1) [6].…”
Section: Introductionmentioning
confidence: 99%